RESULTS OF NON-INVASIVE ACTIVATION MAPPING OF THE HEART IN “IDIOPATHIC” VENTRICULAR ARRHYTHMIAS IN COMPARISON WITH STRUCTURAL CHARACTERISTICS OF MYOCARDIUM BY MAGNETIC RESONANCE IMAGING - N. A. Mironova; L. H. Yeghiazaryan; О. P. Aparina; T. A. Malkina; O. V. Stukalova; S. A. Bakalov; S. P. Golitsyn (Российский кардиологический журнал, 2018)
Aim. To compare the results of non-invasive activational mapping in patients with “idiopathic” ventricular arrhythmias (IVA) with the data on myocardial structure obtained by late enhancement magnetic resonance tomography (MRI).Material and methods. Twenty eight IVA patients, mean age 37 y. o. [26; 45], with ventricular arrhythmias of the heart (VA) of 2nd or higher grade by Lown, and 5 healthy volunteers (HV), mean age 29 [29; 30], underwent surface epiand endocardial non-invasive mapping (SEENIM) of the heart with the system for noninvasive electrophysiological investigation of the heart “Amicard 01C” with the analysis of duration of the activation-recovery interval (ARI) of the ventricles, and high resolution MRI (voxel 1,25x1,25x2,5mm) with delayed contrasting.Results. The number of VA in IVA group was 20196 [11479; 29834] for 24 hours. In 11 patients there were episodes of non-sustained ventricular tachycardia (VT). By SEENIM, predominating morphological type of ventricular ectopic activity in 22 patients sourced from the right ventricle myocardium (RV), of those in 20 from outflow tract of the LV (OTLV). There was significantly prolonged ARI in OTLV patients with IVA comparing to HV (p<0,05). In IVA and non-sustained ventricular tachycardia patients, by contrast MRI of the heart, in LV myocardium there were small foci of contrast retention found. There was no correlation of the areas of contrast retention and topography of VA sources.Conclusion. In most of IVA patients the source of VA was outflowing tract of the RV. The revealed prolongation of the ARI of this area in IVA patients can be an important factor of IVA onset. Small foci of LV fibrosis, found in late enhancement MRI of the heart and episodes of so called idiopathic VT, might be the earliest presentation of the “tachycardiopathy” at the step of pathology development when there are no signs of LV dilation.